(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Brain stem glioma is one of the diseases of CNS. It is brain and spinal cord tumor. It is a type of tumor caused when healthy cells in the brain stem change and increase abnormally and forms a mass that mass called as tumor. This tumor may be malignant. It grows abnormally and spread other parts of body. Glioma is a tumor, it grows from glial cell is supportive cell in the brain. A 13 year old male patient presented in neurology ward with the chief complaint of difficulty chewing and swallowing food, drooping of the face on left side, difficulty while talking, weakness in the left arms and legs, unable to walk along with Headache and Vomiting. After examination and specific investigation following blood test, cytology and MRI scan, the patient was diagnosed as brain stem glioma. Initial management was done by Physician by antibiotic, intravenous fluid, some vitamin and nutritional supplement and diuretics to remove fluid into body. Following the appropriate treatment patient’s condition improved day by day.